C.2 - "Lyon, Peter" (Bombay, 1964)
Neutralism - dissociation from the Cold War - can take many forms. As a doctrine it is to be found in its most comprehensive forms in Asia and Africa; and because its chief proponents are leaders of their countries, it is a profoundly pragmatic and eclectic doctrine. Yet it is deeply grounded in certain widespread hopes and fears, and is usually nourished by nationalism. Neutralist foreign policies are shaped by, and yet have come to shape, the style and scope of Cold War rivalries. Six forms of policy neutralism may be distinguished. These are: new state neutralism; pioneer neutralism; neutralization; buffer status; traditional neutrality; and erstwhile isolationism. Each of these types of policy represents different ways in which a state can become neutralist, and it is suggested how many- states fall into each of these classes. Nearly three quarters of the neutralist states in early 1961 are new states which have become independent since 1945* Many of them practise policies which are in some respects like those of three pioneer neutralists - India, Yugoslavia and Egypt. Since 1945 neutralism has been of growing significance internationally.
Keywords: Neturalism